Optical Density Variations and Microscopic Observations in the Evaluation of Platelet Shape Change and Microaggregate Formation - Kitek, A; Breddin, K (Thrombosis and Haemostasis, 1980)
Addition of Ristocetin to formalin-fixed platelets suspended in diluted PPP induces a marked increase in turbidity which is not caused by platelet shape change but by the formation of microaggregates. If diluted PPP of patients with severe von Willebrand's disease is used, only an initial increase in turbidity and no further decrease is observed without any form variation of the platelets but again with formation of many microaggregates. In normal PRP diluted with buffered EDTA, ADP induces an increase in turbidity without further changes in optical density. Simultaneously platelets immediately change their shape with formation of pseudopodes and sphering but at the same time also microaggregates appear. Shape change and microaggregate formation can also be observed after the addition of Collagen to undiluted PRP which is followed by the formation of large aggregates and a decrease in optical density. Increase in optical density in undiluted PRP is not a specific indicator of platelet shape changes. Microaggregates can alone or partially be responsible for these changes. For the evaluation of platelet shape changes but also for the estimation of microaggregate formation microscopic methods are preferred.
Keywords: Platelet shape change; Aggregation; Microaggregate formation; Formalin-fixed platelets; Optical density